Qallunology101: A lesson plan for the Non Indigenous - Derek Rasmussen (Buddhist Peace Fellowship (Turning Wheel Media), 2013)
Some thoughts about what makes non-Indigenous people so unusual--there has never been a non-Indigenous civilization before in history. What are the effects of peoples who move location on average every 5 or 6 years, with little or no knowledge of the local plants, animals, waterways and lands, and no loyalty to them? Given the worldwide impact of non-Indigenous peoples and their economic system, why are there no Departments of non-Indigenous Studies? This article proposes a draft curriculum.